Risk of tuberculosis after initiation of antiretroviral therapy among persons with HIV in Europe - Johansen, Isik S.; Roen, Ashley; Kraef, Christian; Martín-Iguacel, Raquel; Nemeth, Johannes; Fenner, Lukas; Zangerle, Robert; Llibre, Josep M.; Miller, Robert F.; Suarez, Isabelle; de Wit, Stephane; Wit, Ferdinand; et al. (International journal of infectious diseases, 2024)
•The tuberculosis (TB) risk after antiretroviral treatment (ART) initiation in Europe is studied.•TB peaked within 3 months post ART (14.41/1000 PY).•TB was linked to certain baseline risk factors.•TB risk declined over time but remained above European background.•Thorough TB risk assessment essential at ART onset. Tuberculosis (TB) risk after initiation of antiretroviral treatment (ART) is not well described in a European setting, with an average TB incidence of 25/105 in the background population. We included all adult persons with HIV starting ART in the RESPOND cohort between 2012 and 2020. TB incidence rates (IR) were assessed for consecutive time intervals post-ART initiation. Risk factors for TB within 6 months from ART initiation were evaluated using Poisson regression models. Among 8441 persons with HIV, who started ART, 66 developed TB during 34,239 person-years of follow-up (PYFU), corresponding to 1.87/1000 PYFU (95% confidence interval [CI]: 1.47-2.37). TB IR was highest in the first 3 months after ART initiation (14.41/1000 PY (95%CI 10.08-20.61]) and declined at 3-6, 6-12, and >12 months post-ART initiation (5.89 [95%CI 3.35-10.37], 2.54 [95%CI 1.36-4.73] and 0.51 [95%CI 0.30-0.86]), respectively. Independent risk factors for TB within the first 6 months after ART initiation included follow-up in Northern or Eastern Europe region, African origin, baseline CD4 count <200 cells/mm3, HIV RNA >100,000 copies/mL, injecting drug use and heterosexual transmission. TB IR was highest in the first 3 months post-ART initiation and was associated with baseline risk factors, highlighting the importance of thorough TB risk assessment at ART initiation.